2020
DOI: 10.3390/ijerph17061882
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Scale for Partnership in Care—for Family (SPIC-F)

Abstract: This study aims to develop and validate the Scale for Partnership in Care between staff and families of older adult nursing home (NH) residents—for Family (SPIC-F). The components of partnership were identified on the basis of literature reviews and focus group interviews. The content validity of 41 preliminary items was verified by 10 experts, and a pilot study was conducted. The reliability and validity of the instrument was tested on 330 families of older adult NH residents. The final instrument comprised 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(61 reference statements)
0
4
1
Order By: Relevance
“…Similarly, failing to extract the fourth ( providing tailored care ) dimension as a discriminant dimension is in the same context as other partnership scales for families in the nursing field that show a high correlation between dimensions. 20 However, our finding contrasts with those of another study on the SHC Partnership Scale for School Nurses, wherein this dimension demonstrated commonality as a unique dimension. 53 The finding that school nurses have clearer boundaries about the nature of the SHC partnership compared with parents can be explained by differences in parents’ and nurses’ experiences, perspectives, and literacy regarding SHC partnerships.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Similarly, failing to extract the fourth ( providing tailored care ) dimension as a discriminant dimension is in the same context as other partnership scales for families in the nursing field that show a high correlation between dimensions. 20 However, our finding contrasts with those of another study on the SHC Partnership Scale for School Nurses, wherein this dimension demonstrated commonality as a unique dimension. 53 The finding that school nurses have clearer boundaries about the nature of the SHC partnership compared with parents can be explained by differences in parents’ and nurses’ experiences, perspectives, and literacy regarding SHC partnerships.…”
Section: Discussioncontrasting
confidence: 99%
“…Items 5, 25, 27, 36, and 37 were removed because they had an extreme ceiling effect of over 45% and also exceeded the cutoff values for both Z skewenss and Z kurtosis . Items 3,4,6,15,17,20,23, and 28 to 31 were removed to reduce redundancy, as they had multi-item correlations of over .75 (Supplementary Table 2). Ultimately, 25 items were retained.…”
Section: Validity Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…This factor can also be found in the measurement tool for families' perspective partnership with staff within long‐term care facilities. This finding indicates that collaborative relationship and communication are important components for partnership, and they can be evaluated from both staff and families’ perspectives (Jang & Song, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This Special Issue also comprises intervention studies, with interventions aimed at addressing depressive symptoms in nursing home residents [10,11], adjustment for new residents [12], social and psychological support [13], and loneliness and isolation [14]. Other studies present evidence which developed and tested quality indicators [15,16], and tools which capture the experience of quality from a resident's perspective [17,18], and assess partnership working between staff and families [19]. We also included studies that investigated factors associated with older people's experiences, such as the association between length of stay and end of life care [20], dry eyes or ocular lubricants with medication use, dementia, frailty and dry eyes [21], resident characteristics and their palliative care service use and comfort in the last week of life [22] and causes of infection-related hospitalizations [23].…”
mentioning
confidence: 99%